The Effects of Different Pressure Pneumoperitoneum on the Pulmonary Mechanics and Surgical Satisfaction in the Laparoscopic Cholecystectomy - B. Küçüköztaş; L. İyilikçi; S. Ozbilgin; M. Ozbilgin; T. Ünek; H. Ellidokuz (Общая реаниматология)
Objectives. Inspiratory, hemodynamic and metabolic changes occur in laparoscopic surgery depending on pneumoperitoneum and patient position. This study aims to evaluate the effects of intra-abdominal pressure increase based on CO2 pneumoperitoneum in laparoscopic operations on hemodynamic parameters and respiratory dynamics and satisfaction of surgeon and operative view.Materials and Methods. A total of 116 consecutive, prospective, ASA class I–III cases aged 18–70 years undergoing laparoscopic cholecystectomy were enrolled in this study. Data of 104 patients were analysed. Patients were divided into two groups as the group Low Pressure (<12 mmHg) (Group LP) (n=53) and the group Standard Pressure (>13 mmHg) (Group SP) (n=51). In this study administration of general anesthesia used total intravenous anaesthesia in both groups. All groups had standard and TOF monitorization applied. The anaesthesia methods used in both groups were recorded. Before, during and after peritoneal insufflation, the peroperative ventilation parameters and hemodynamic parameters were recorded. The adequacy of pneumoperitoneum, gastric and the operative view were evaluated by the operating surgeon and recorded.Results. The peripheral oxygen saturation showed no significant difference between the low and standard pressure pneumoperitoneum in view of tidal volume, respiratory rate, end tidal CO2, mean and peak inspiratory pressure, and minute ventilation values. In terms of hemodynamics, when values just after intubation and before extubation were compared, it was observed that in the LP group systolic, diastolic and mean blood pressure values were higher. In terms of heart rate, no significant difference was observed in determined periods between groups. There was no significant difference between the groups in terms of surgical satisfaction and vision.Conclusion. Low pressure pneumoperitoneum provides effective respiratory mechanics and stable hemodynamics for laparoscopic cholecystectomy. It also provides the surgeon with sufficient space for hand manipulations. Anaesthetic method, TIVA and neuromuscular blockage provided good surgery vision with low pressure pneumoperitoneum.